Nitric oxide enhancement supplement containing beet nitrite and nitrate benefits high intensity cycle interval training - Broeder, C. E.; Flores, V.; Julian, B.; Wojan, F.; Tauber, R.; Schubert, L.; Salacinski, A.; Ivy, J. L. (Current Research in Physiology, 2021)
This study investigated the effects of a beet nitric oxide enhancing (NOE) supplement comprised of nitrite and nitrate on cycling performance indices in trained cyclists. Methods: Subjects completed a lactate threshold test and a high-intensity interval (HIIT) protocol at 50% above functional threshold power with or without oral NOE supplement. Results: NOE supplementation enhanced lactate threshold by 7.2% (Placebo = 191.6 ± 37.3 W, NOE = 205.3 ± 39.9; p = 0.01; Effect Size (ES) = 0.40). During the HIIT protocol, NOE supplementation improved time to exhaustion 18% (Placebo = 1251 ± 562s, NOE = 1474 ± 504s; p = 0.02; ES = 0.42) and total energy expended 22.3% (Placebo = 251 ± 48.6 kJ, NOE = 306.6 ± 55.2 kJ; p = 0.01; ES = 1.079). NOE supplementation increased the intervals completed (Placebo = 7.00 ± 2.5, NOE = 8.14 ± 2.4; p = 0.03; ES = 0.42) and distance cycled (Placebo = 10.9 ± 4.0 km, NOE = 13.5 ± 3.9 km; p = 0.01; ES = 0.65). Also, target power was achieved at a higher cadence during the HIIT work and rest periods (p = 0.02), which enhanced muscle oxygen saturation (SmO2) recovery. Time-to-fatigue was negatively correlated with the degree of SmO2, desaturation during the HIIT work interval segment (r = -0.67; p 0.008), while both SmO2 desaturation and the SmO2 starting work segment saturation level correlated with a cyclist's kJ expended (SmO2 desaturation: r = -0.51, p = 0.06; SmO2 starting saturation: r = 0.59, p = 0.03). Conclusion: NOE supplementation containing beet nitrite and nitrate enhanced submaximal (lactate threshold) and HIIT maximal effort work. The NOE supplementation resulted in a cyclist riding at higher cadence rates with lower absolute torque values at the same power during both the work and rest periods, which in-turn delayed over-all fatigue and improved total work output.